Accountability in the social economy: the case of private social solidarity institutions - Ferreira, Augusta (2022)
Given the extreme importance of improving the accountability of private social solidarity institutions (IPSS), both for reasons of legal compliance and for reasons of improving legitimacy and notoriety among their stakeholders, in order to be accountable to them and in order to maintain their sustainability, this article aims to present a framework designed under a more comprehensive research project for the assessment of IPSS accountability, as well as the preliminary results of a pilot test of Portuguese IPSS. The framework was developed from a combination of methodologies that included a literature review, field work and a focus group, resulting in six dimensions with 76 indicators. For the pilot test, the data were collected by questionnaire for the years 2018, 2019 and 2020. The results of the pilot test, despite the limited number of entities, allowed the identification of some trends and indicators where entities show lower results and where they will have to focus to improve their accountability. Some possible effects of the COVID-19 pandemic were also identified. Therefore, we believe that the framework designed answers the research question: how can we promote accountability (social, financial and economic) in the social economy sector, in particular in the case of IPSS?